Desarrollo de video juego en Unity 2D para el apoyo de la estimulación de la conciencia fonológica en niños de 4 a 6 años de edad (2021)
Phonological awareness includes the skill of operating with word segments, that is, segmenting words into smaller units, such as syllables, phonemes, and intrasyllabic units. Reading needs teaching, unlike language, which is a natural learning process. It requires an enormously sophisticated cognitive system that only functions correctly once all the elements of the system are in place. In order to learn to read and write, the child requires some primordial prerequisites, among them is phonological awareness. If any of the elements fail, reading and writing ceases to be an expeditious and instantaneous activity and becomes something difficult that requires great effort, leading to learning problems. The objective of this project was to develop a video game on the Unity 2D platform that stimulates phonological awareness in children from 4 to 6 years old in order to improve the learning of reading and writing. Rehabilitation engineering through the creation of a video game can facilitate and support the work of professionals in the field of health and education, contributing to children's access to important knowledge, such as reading and writing, contributing to the emotional, social and educational development of children. The direct population that benefited are children between 4 and 6 years of age in kindergarten, preschool and first grade. First, a theoretical research and interviews with professionals in the field of speech therapy were carried out. After gathering this information with the support of professionals in the area, we proceeded to design and create activities that promoted the stimulation of skills at two levels of phonological awareness, syllabic awareness and phonemic awareness. The validation of this project was carried out by professional speech therapists and an engineer expert in the design of applications through rubrics and PECFO (test that evaluates the level of phonological awareness in which the child is), this test was applied at the beginning and at the end of the video game as an evaluator of the performance that the users had before and after the execution of Ruago Game; in this way it was possible to support the stimulation of phonological awareness of three children through the use of this tool.